If it's not what You are looking for type in the equation solver your own equation and let us solve it.
0.6(x+6)=11
We move all terms to the left:
0.6(x+6)-(11)=0
We multiply parentheses
0.6x+3.6-11=0
We add all the numbers together, and all the variables
0.6x-7.4=0
We move all terms containing x to the left, all other terms to the right
0.6x=7.4
x=7.4/0.6
x=12+0.2/0.6
| 4(2+y)-3y=1 | | 847-h=327 | | 7=s/6-1 | | -8(4v+2)=176 | | 2w^2+6w-520=0 | | m/10+49=57 | | x^2+√5x-19=0 | | 1,2(3x+6)=-4 | | 6(4x+5)=40x+14 | | 1+4(2x-1)=6.25x+26 | | 30-5kk=-2 | | 6d-30=42 | | 8=56/w | | 66+y-8+y+6=180 | | 96-j=44 | | 4(y-3)=5y+51 | | 12(2x32-3)=6(32) | | (3x)+(5x-64)=180 | | 1=m+6/20 | | 62+61+19v=180 | | 30+3u=96 | | 2w^2+10w-651=0 | | 44+6s+2s=180 | | 4x+6−7x+9=18 | | 7x+4×=-66 | | 3n+1n=-6 | | 106+44+2z=180 | | 2w^2+32w-6144=0 | | 29-q=10 | | t+15=85 | | p–(-27)=13 | | t-15=85 |